MANAJEMEN PENANGANAN KONSTRUKSI JALAN RAYA (STUDI KASUS JALAN SYIAH KUALA BANDA ACEH) - Afrizal Afrizal; Sofyan M. Saleh; Noer Fadhly (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2012)
Abstract: The establishment of Lampulo as the fishing industrial area in Banda Aceh spatial improvements in the management of Coastal Fishery Port (PPP) to the Ocean Fishery Port (PPS) affects the growth of traffic volume on Jalan Syiah Kuala. The study was conducted on a segment of the Jalan Syiah Kuala. The research objective is to analyze the performance of road maintenance management, upgrading of roads to assess the feasibility to perform analysis of Vehicle Operating Costs (BOK), the capacity of the road and the IRI (International Rougnhness Index). Analysis based on the guideline calculations in MKJI 1997. The analysis shows that traffic growth is analyzed by the two scenarios, namely the growth of normal (Do Nothing) and the growth development of the area (Do Something). Do Nothing Jalan Syiah Kuala is rising the traffic growth that need to be handled with four alternatives: (1) analysis of the performance of existing road conditions do minimum (2/2 UD) in 2010 to 2014; (2) alternative A handling (2/2 UD) 2015, to 2016, (3) alternative B (4/2 D) in 2017 to 2021 and (4) alternative C (6/2 D) in 2022 to 2024. Jalan Syiah Kuala needs to have a good way of handling to maintain the degree of saturation as the ratio of traffic flow on road capacity remains below 0.75. For the development activity in Lampulo, it needs to be done with four alternatives: 1) analysis of existing road conditions (2/2 UD) of 2010 to 2013; 2) alternative A (4/2 D) 2014, s / d 2019; 3) alternative B (6/2 D) in 2020 to 2021, 4) alternative C (6/2 D) increase the width of the strip in 2022 to 2024. Methods of Syiah Kuala road maintenance carried out by IRI analysis. Routine maintenance of normal growth carried out each year and periodically in 2022, growth in the development of the periodic maintenance performed in 2021. Recommended to the city of Banda Aceh Public Works to manage the handling of Jalan Syiah Kuala future maintenance and reconstruction plans.Keywords : management, street performance, maintenance, financingAbstrak: Penetapan Lampulo sebagai kawasan industri perikanan dalam tata ruang Banda Aceh dengan peningkatan status pengelolaan Pelabuhan Perikanan Pantai (PPP) menjadi Pelabuhan Perikanan Samudera (PPS) berdampak terhadap pertumbuhan volume lalu lintas pada Jalan Syiah Kuala. Penelitian dilakukan pada ruas Jalan Syiah Kuala. Tujuan penelitian adalah menganalisis kinerja jalan terhadap manajemen pemeliharaan, peningkatan jalan dengan mengkaji tingkat kelayakan dengan melakukan analisis Biaya Operasional Kendaraan (BOK), kapasitas jalan dan IRI (Internasional Rougnhness Index). Analisa berdasarkan pedoman perhitungan dalam MKJI 1997. Hasil analisis menunjukkan bahwa pertumbuhan lalu lintas dikaji dengan dua scenario yaitu pertumbuhan normal (Do Nothing) dan pertumbuhan pengembangan kawasan (Do Something). Do Nothing Jalan Syiah Kuala pertumbuhan lalu lintas meningkat sehingga perlu penanganan jalan dengan 4 alternatif, yaitu 1) analisa kinerja jalan kondisi existing do mínimum (2/2 UD) pada tahun 2010 s/d 2014; 2) penanganan alternatif A (2/2 UD) tahun 2015 s/d 2016; 3) alternatif B (4/2 D) tahun 2017 s/d 2021 dan 4) alternatif C (6/2 D) tahun 2022 s/d 2024. Penanganan Jalan Syiah Kuala perlu dilakukan untuk mempertahankan derajat kejenuhan sebagai rasio arus lalu lintas terhadap kapasitas jalan tetap dibawah 0,75. Untuk aktivitas pengembangan kawasan Lampulo perlu dilakukan penanganan jalan dengan 4 alternatif, yaitu 1) analisa jalan kondisi existing (2/2 UD) tahun 2010 s/d 2013; 2) alternatif A (4/2 D) tahun 2014 s/d 2019; 3) alternatif B (6/2 D) tahun 2020 s/d 2021; 4) alternative C (6/2 D) penambahan lebar lajur tahun 2022 s/d 2024. Metode pemeliharan Jalan Syiah Kuala dilakukan dengan analisa IRI. Pertumbuhan normal dilakukan pemeliharan rutin setiap tahun dan berkala pada tahun 2022, pertumbuhan pengembangan kawasan dilakukan pemeliharan berkala tahun 2021. Disarankan kepada Dinas PU kota Banda Aceh untuk melakukan manajemen penanganan Jalan Syiah Kuala dimasa mendatang pemeliharaan dan rencana rekontruksi.Kata kunci : Manajemen, kinerja jalan, pemeliharaan, pembiayaan